Model-Driven Development of WSN Applications - Becker, L. B.; Basso, F. P.; Fröhlich, A. A.; Paulon, A. R. (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2013: Anais do III Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2013)
Wireless Sensor Networks (WSNs) are rapidly becoming a necessary tool in many different application areas, such as environmental monitoring, security, safety, and so on. The heterogeneity of hardware is large, so there exists several different environments that support WSN programming. However, the great majority of such environments only target the sensors programming, forgetting about their real intent: the application. In this paper we propose an approach to satisfy the need of high level development methods in WSN applications, aiming to provide a clear link between the modeled WSN constraints and the programming entities. An important part of this proposal is the so-called WiSeN Profile, an UML profile devoted for WSN applications design in a Model-Drivel Development (MDD) paradigm.